EFEKTIFITAS METODE TUTOR TEMAN SEBAYA UNTUK MENINGKATKAN KEMAMPUAN MANDI ANAK TUNAGRAHITA SEDANG X - Sarip Suzar’an (Universitas Negeri Padang, 2016)
ABSTRACT The problem of this research was a student with medium mental retardation named X who had problems to take a bath. He got less attention from his family as most of them also has medium mental retardation. To take care of himself, X was assisted by his aunt. Meanwhile his father did not live with him anymore. This research then was intended to prove the effectiveness of peertutoring method to increase the ability of student with medium mental retardation (X) to have a bath at SDLB 64 Surabayo Kecamatan Lubuk Basung. This research applied experimental method and A-B-A design. The subjects of the research was a student in class D6/ C1 SDLB 64 Surabayo Kecamatan Lubuk Basung. The date were collected through observation. The istrument consisted of 10 items. The data gotten were analyzed by using visual analysis of graphic. The research was conducted in 26 meetings and three conditions (A-B-A). In the baseline condition I (A-1) that consisted of 7 observations, the student’s score was 10%. In the intervention condition (B) that consisted of 12 observations, the student’ score was between 10%-80%. In the baseline condition II (A-2) that consisted of 7 observations, the student’ score was between 80% - 90%. Hence, it was proved that the use of peer-tutoring method could increase the ability of the student with medium mental retardation (X) to have a bath at SDLB Negeri 64 Surabayo Kecamatan Lubuk Basung. Therefore, it was suggested to the teachers to improve the quality of educational services for the students with medium mental retardation so that they could do daily activities independently. Kata kunci : Mandi, Tutor Teman Sebaya, Anak Tunagrahita Sedang, SDLB Negeri 64 Surabayo